Proximal Tibial Bone Metastases in Patient with Breast Carcinoma: A Rare Case Report - Yadav, Ajay Kumar; Chaudhary, mardeep; Raymajhi, Asmita; Adhikari D, Ganga (Nepal Journal of Health Sciences, 2026)
Background: Bone metastases from any carcinoma below elbow and knee are rare, those to tibia are even rarer. Diagnosis sometimes may defer and often confused with primary bone carcinoma, osteomyelitis or arthritis. Management depends on extent of disease and severity of symptoms. Both radical and palliative treatment are possible, depending on the overall clinical severity. Case Presentation: We present a case of a 41-year female patient with a history of right breast carcinoma. Previously, the patient was misdiagnosed as right breast fibroadenoma with sebaceous cyst, a mass measuring 13.1x9.5x6.7 mm3. The patient was then advised to have an excisional biopsy of whole solid mass and mass was sent for histopathology examination to get clear opinion. The histopathology report revealed that there was cribriform ductal carcinoma in situ intermediate nuclear grade. Before starting any treatment, the patient is advised to have all the required laboratory examinations, CECT chest abdomen and 99mTc-MDP whole body bone scan. Whole body bone scan revealed that there is osteoblastic lesion in shaft of right proximal tibia suggestive of bone metastases. Later it was confirmed with histopathology report. Conclusion: Proximal tibial bone metastasis in a patient with breast carcinoma is a relatively very uncommon, but challenging, site for bone metastasis.